Anaerobic Solid-State Fermentation of Soybean Meal With Bacillus sp. to Improve Nutritional Quality - Yao, Yanhui; Li, Hongya; Li, Jia; Zhu, Baocheng; Gao, Tongguo (Frontiers in Nutrition, 2021)
The study evaluated the impact of fermentation with Bacillus sp. on nutritional quality of soybean meal (SBM) and the changes of bacterial community structure during fermentation. High-producing protease strains were screened for degrading SBM macromolecular protein and anti-nutritional factor (ANFs). Unsterilized SMB then underwent anaerobic solid fermentation method to evaluate the effects of fermentation. Results showed that for the 9 high-producing protease strains that were screened, acid soluble protein contents in fermented soybean meal all increased, with the highest value found to be 13.48%, which was fermented using strain N-11. N-11 was identified as Bacillus subtilis. N-11 fermentation reduced ANFs such as glycinin and β-conglycinin by 82.38% and 88.32%, respectively. During N-11 fermentation, the bacterial richness and diversity in soybean meal increased, but not significantly. The high-yield protease strain B. subtilis N-11 selected in this experiment, improved nutritional quality of SBM through fermentation, and can be used for industrial large-scale production.